Synthesis of 1-(5-(4-chlorophenyl)-1-(2,4-dichlorophenyl)-4-methyl-1H-pyrazol-3-yl)-2-morpholinoethane-1,2-dione analogues and their inhibitory activities with reduced cytotoxicity in lipopolysaccharide-induced BV2 cells - Yoon, Sung Hwa; Cho, Duk Yeon; Han, Jun Hyuk; Choi, Dong Kug; Kim, Eunha; Park, Ju Young (Bioorganic and Medicinal Chemistry Letters, 2023)
A series of rimonabant analogues, where the N-aminopiperidine moiety was replaced by various amines and an additional carbonyl group, were synthesized and their inhibition of nitric oxide (NO) production was evaluated in lipopolysaccharide (LPS)-induced BV2 microglial cells. Among the synthesized compounds, the morpholine analogue 7y (IC50 = 4.71 ± 0.11 μM) showed significantly higher inhibitory activity than rimonabant (IC50 = 16.17 ± 0.56 μM), and suppressed NO production dose-dependently without cytotoxicity. In addition, 7y inhibited the expression of iNOS, COX-2 and pro-inflammatory cytokines and attenuated LPS-induced activation of nuclear factor-kappa B (NF-κB) and ERK MAPK phosphorylation in BV2 cells. These results demonstrated that 7y exerted anti-inflammatory effects by ERK pathway in BV2 cells, which can be used for the prevention and treatment of neuroinflammatory diseases.
Keywords: Anti-Inflammatory Agents; Cyclooxygenase 2; Lipopolysaccharides; Microglia; NF-kappa B; Nitric Oxide; Nitric Oxide Synthase Type II; Rimonabant; Anti-inflammatory effect; BV2 cell; Oxoacetamide analogues